A Framework for Establishing Restoration Goals for Contaminated Ecosystems - Wagner, Anne M.; Larson, Diane L.; DalSoglio, Julie A.; Harris, Jim A.; Labus, Paul; Rosi-Marshall, Emma J.; Skrabis, Kristin E. (Wiley, 2015)
As natural resources become increasingly limited, the value of restoring contaminated sites, both terrestrial and aquatic, becomes increasingly apparent. Traditionally, goals for remediation have been set before any consideration of goals for ecological restoration. The goals for remediation have focused on removing or limiting contamination whereas restoration goals have targeted the ultimate end use. Here, we present a framework for developing a comprehensive set of achievable goals for ecological restoration of contaminated sites to be used in concert with determining goals for remediation. This framework was developed during a Society of Environmental Toxicology and Chemistry (SETAC) and Society of Ecological Restoration (SER) cosponsored workshop that brought together experts from multiple countries. Although most members were from North America, this framework is designed for use internationally. We discuss the integration of establishing goals for both contaminant remediation and overall restoration, and the need to include both the restoration of ecological and socio-cultural-economic value in the context of contaminated sites. Although recognizing that in some countries there may be regulatory issues associated with contaminants and clean up, landscape setting and social drivers can inform the restoration goals. We provide a decision tree support tool to guide the establishment of restoration goals for contaminated ecosystems. The overall intent of this decision tree is to provide a framework for goal setting and to identify outcomes achievable given the contamination present at a site. Integr Environ Assess Manag 2016;12:264–272. 2015 The Authors. Integrated Environmental Assessment and Management published by Wiley Periodicals, Inc. on behalf of Society of Environmental Toxicology & Chemistry (SETAC)
This article represents 1 of 6 articles in the special series “Restoration of Impaired Ecosystems: An Ounce of Prevention or a Pound of Cure?” The articles result from a Technical Workshop organized by SETAC and the Society for Ecological Restoration, held June 2014 in Jackson, Wyoming, that focused on advancing the practice of restoring ecosystems that have been contaminated or impaired from industrial activities.
Keywords: Decision support; Remediation; Restoration; Restoration Goals